Efeito do plasma rico em plaquetas e da eritropoietina na regeneração do nervo ciático de ratos wistar - Colomé, Lucas Marques (2012)
Injuries to the peripheral nervous system present a challenge for regenerative medicine. The study investigated the effects of platelet-rich plasma (PRP) and erythropoietin (EPO), alone or in combination, in the regeneration of peripheral nerve in rats. The work was developed in three phases using 70 rats. The first phase, evaluated the platelet concentration and growth factors production/release (TGF-β, PDGF, VEGF and αβ) in three protocols for obtaining PRP (A, B and C) obtained by aortic or cardiac puncture. Cardiac puncture in association with A protocol showed the best results. In the second stage, using best results methods at the first stage, was produced two PRP concentrations (1,000,000 and 2,000,000 platelets.μl-1; PRP1 and PRP2, respectively) for applying in the rats sciatic nerve. Comparison of concentrations with autologous nerve graft (ANG) and saline solution (SS) groups showed benefits in the use of PRP2. In the third phase (same experimental model) were added PRP2 + EPO and EPO groups. The animals of phases 1 and 2 were evaluated by walking track test and histomorphometric analysis (toluidine blue) and showed benefits in autologous nerve graft (ANG) with respect to tubulization (independent of regenerative factor). For tubularized animals, the study showed advantages for PRP and EPO simultaneous use followed by EPO group. Finally, it was observed that PRP 2,000,000 platelets.μl-1 has beneficial effects when compared to PRP 1,000,000 platelets.μl-1 for peripheral neuroregeneration rats.